Principales cultivares de judía verde (Phaseolus vulgaris L.), que se siembran en el Ecuador - Bonifaz Vera, Jordy Jilmar (2020)
This paper was carried out with the purpose of analyzing the main types of cultivars of green beans that exist in Ecuador, due to the farmer's lack of knowledge about them, therefore, each of the most cultivars in the country was described, where Their morphological characteristics, origin, taxonomy, climatic adaptation and their production yield were indicated. All this with the aim of improving the economic situation of the farmer and therefore of the Country. In addition, the nutritional benefits obtained from this vegetable were studied, since when ingested it provides high amounts of proteins, vitamins and essential minerals, which means that green beans could be a very nutritious food such as meat products, even this vegetable has a certain advantage by keeping its price stable within the local market, which contributes to the food security and sovereignty of Ecuadorians.